2005
DOI: 10.1021/cm0503230
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for the Preparation of Polymeric Hollow Nanospheres Containing Silver Cores with Different Sizes

Abstract: A novel photoreduction method is presented in this paper for the fabrication of polypyrrole-chitosan (PPy-CS) hollow nanospheres with movable Ag nanoparticles inside (Ag@PPy-CS). Ag nanoparticle is formed by ultraviolet irradiation in the interior of the PPy-CS hollow nanosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 29 publications
5
100
0
2
Order By: Relevance
“…Cheng et al prepared Ag@polypyrrole-chitosan (PPy-CS) nanorattles by photoreduction of Ag þ with CS. [316] In this case, only the silver salt is required to diffuse into the PPy-CS nanoreactors since one component of the shells can serve as the reducing agent. Moreover, the amount of AgNO 3 loaded into the nanoreactors can be easily controlled by adjusting the pH-sensitive permeability of the polymer shells.…”
Section: Reviewmentioning
confidence: 99%
“…Cheng et al prepared Ag@polypyrrole-chitosan (PPy-CS) nanorattles by photoreduction of Ag þ with CS. [316] In this case, only the silver salt is required to diffuse into the PPy-CS nanoreactors since one component of the shells can serve as the reducing agent. Moreover, the amount of AgNO 3 loaded into the nanoreactors can be easily controlled by adjusting the pH-sensitive permeability of the polymer shells.…”
Section: Reviewmentioning
confidence: 99%
“…After polymeriza- tion and removal of silica, spherical poly(divinyl benzene) capsules encapsulating AuNPs were fabricated. In addition, Cheng et al [6] developed a relatively simple photoreduction process to synthesize silver-encapsulated hollow polypyrrole-chitosan spheres. Although the template-assisted approach and other protocols mentioned above offer promising ways to create polymer capsules that encapsulate a single metal nanoparticle, they involved rather complex synthesis procedures and rigorous control of reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As Cheng et al 14 UV-visible spectrophotometry ( max = 639 nm) showed that the encapsulation by adsorption was successful, with 88% efficiency under the conditions described in section 2.4. The Nile blue chlorideloaded ppy-chit hollow nanospheres were also characterized by ATR-IR and AFM.…”
Section: Model Drug Uptake and Characterisation Of Loaded Nanoparticlesmentioning
confidence: 86%